2020
DOI: 10.21203/rs.3.rs-24026/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of health literacy and self-care behaviors on health-related quality of life in Iranians with type 2 diabetes: a cross-sectional study

Abstract: Background Regarding the importance of health literacy as a key factor in self-care, appropriate understanding of health information by patients with type 2 diabetes mellitus (T2DM) is fundamental for better management of risk factors, which can also benefit their quality of life. This study aimed to describe the relationship between health literacy (HL), and self-care behaviors with health-related quality of life (HRQL) in patients with T2DM. Methods A cross-sectional survey was done in Iran in 2019. Patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It has been predicted that around 11.4% of the Iranian adult population has diabetes mellitus, and by 2030, around 9 million Iranians will be at risk of developing diabetes mellitus [15]. Approximately 80% of diabetic patients in developing countries live in deprived and less developed regions [15].…”
Section: Type II Diabetesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been predicted that around 11.4% of the Iranian adult population has diabetes mellitus, and by 2030, around 9 million Iranians will be at risk of developing diabetes mellitus [15]. Approximately 80% of diabetic patients in developing countries live in deprived and less developed regions [15].…”
Section: Type II Diabetesmentioning
confidence: 99%
“…The prevalence of diabetes in Iran is 3.0, 5.8, 10.8, 14.0% in men and 3.0, 7.0, 14.0, and 19.4% in women aged 25-34, 35-44, 45-54, and 55-64 years, respectively [16]. It has been predicted that around 11.4% of the Iranian adult population has diabetes mellitus, and by 2030, around 9 million Iranians will be at risk of developing diabetes mellitus [15]. Approximately 80% of diabetic patients in developing countries live in deprived and less developed regions [15].…”
Section: Type II Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Seyedoshohadaee et al (2015) found no signi cant correlation between health literacy and self-care behaviors [13]. Several studies suggest that health literacy (HL) plays a signi cant role in adherence to diabetes self-care and outcomes [14,15]. As patients are required to participate in more complicated health care and navigate more complex health systems, their need to be 'health literate' in today's society is more signi cant than ever before [16].…”
mentioning
confidence: 99%